ASSESSMENT OF IMPACT OF INSECURITY ON TEACHER JOB PERFORMANCE IN PUBLIC SCHOOLS IN NIGERIA - Ukpoju Bartholomew Ojochenemi; Cosmas Victor; Abayomi Isaac Araiyegbemi (International Journal of Business, Law and Political Science, 2025)
Objective: To evaluate the impact of insecurity on teacher job performance in Nigerian public schools. Method: A position paper approach was adopted, relying on secondary data collected from print and internet publications. Results: The findings indicate that pervasive insecurity significantly undermines teacher performance, contributing to critical issues such as teacher deaths, kidnappings, and displacement. Novelty: This study uniquely synthesizes secondary data to illuminate the direct correlation between security challenges and educational outcomes, and it advocates for comprehensive governmental interventions at the federal, state, and local levels to bolster safety measures in educational institutions.